Using Jambi Local Wisdom of Lubuk Larangan as Theme for Development of Science Teaching Materials to Improve Students’ Environmental Literacy - Arizaldy, Arizaldy; Anwar, Sjaeful; Sriyati, Siti (Jurnal Pendidikan MIPA, 2022)
This research aims to produce teaching materials on the theme of lubuk larangan using 4S-TMD method to improve students' environmental literacy. The research method used was developmental Research, covering three stages, namely design, development, and evaluation. In the development stage, 4S-TMD method consists of selection, structuring, characterization, and didactic reduction. The instruments used are rubric for selection stage, rubric for structuring stage, rubric for characterization stage, rubric for didactic reduction, rubric for understanding and validation questionnaire for the feasibility of teaching materials.The results of the evaluation of the developed teaching material showed that it was self-instructional. It was easy to understand (85%). In terms of feasibility, the material was very feasible (88,88%). Student environmental literacy can be developed through the task at the end of the learning material in the form of assignments and questions posed on the teaching material which refers to the component of environmental literacy and the context of lubuk larangan. Keywords: teaching material, local wisdom, environmental literacy, 4S-TMD. DOI: http://dx.doi.org/10.23960/jpmipa/v23i1.pp162-172